A COMPARISON BETWEEN THE PECULIARITIES PRESENTED IN - Rosley Anholon; Eugênio José Zoqui; Jefferson de Souza Pinto; Diego de Carvalho Moretti (Revista Produção Online, 2007)
The objective of this paper is to compare the main administrative characteristics of micro and small enterprises present by the literature and observed during the improvement programs implantation in nine companies situated in Jundiaí Business Incubator, São Paulo State. During one year, the authors of this paper have observed administrative deficiencies, such as lacks of strategic planning, confusion between the company and entrepreneur money, influence of family relation in promotion or tasks, and others. On the other hand, good aspects were observed such as flexibility, internal easier communication, good relationship with the clients, and so on. By improvement programs implementation, a lot of deficiencies were reduced or eliminated and the conclusions presented by this paper contribute to the micro and small business literature.